Health design thinking : creating products and services for better health - Ku, Bon.; Lupton, Ellen (2020)
"This book makes a case for applying the principles of design thinking to real-world health care challenges. As health care systems around the globe struggle to expand access, improve outcomes, and control costs, Health Design Thinking offers a human-centered approach for designing health care products and services, with examples and case studies that range from drug packaging and exam rooms to internet-connected devices for early detection of breast cancer. Written by leaders in the field--Bon Ku, a physician and founder of the innovative Health Design Lab at Sidney Kimmel Medical College, and Ellen Lupton, an award-winning graphic designer and curator at Cooper Hewitt Smithsonian Design Museum--the book outlines the fundamentals of design thinking and highlights important products, prototypes, and research in health design. Health design thinking uses play and experimentation rather than a rigid methodology. It draws on interviews, observations, diagrams, storytelling, physical models, and role playing; design teams focus not on technology but on problems faced by patients and clinicians. The book's diverse case studies show health design thinking in action. These include the development of PillPack, which frames prescription drug delivery in terms of user experience design; a credit card-size device that allows patients to generate their own electrocardiograms; and improved emergency room signage. Drawings, photographs, storyboards, and other visualizations accompany the case studies." --Amazon.com.
Human centered -- Empathy -- Codesign -- Social determinants -- Creative mindset -- Questioning -- Visualizing -- Prototyping -- Storytelling -- Design workshop -- Brainstorming -- Interview -- Photo journal -- Persona -- Role-playing -- Role cards -- Storyboard -- Journey map -- Project board -- Data visualization -- Occupancy survey -- Spatial data mapping -- Prescription drug packaging -- Pharmacy redesign -- Surgical procedure trays -- Foley catheter kit -- Hospital garments -- Hospital hacks -- Wearable diagnostics -- iBreastExam -- Newborn Phototherapy -- Behavioral health -- Digital therapeutics -- Digital health record -- Clinical trial design -- Informed consent -- Visual health history -- Shared decision-making -- Personalized asthma care -- Smoke-free homes -- Puberty education -- Demand for chlorhexidine -- Emergency department signage -- Exam room -- Labor and delivery unit -- Cholera treatment center -- Sensory arts garden -- Health design lab -- Medical futures lab -- Health design curriculum -- 3D printing -- Designing medical devices.
Includes bibliographical references (page 218) and index.
Keywords: Health planning; Medical care -- Design; Health facilities -- Design and construction